2019
DOI: 10.3390/en12193707
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Axisymmetric Wave Propagation in Buried Fluid-Filled Pipes for Optimizing the Vibro-Acoustic Technique When Locating Gas Pipelines

Abstract: Buried pipeline systems play a vital role in energy storage and transportation, especially for fluid energies like water and gas. The ability to locate buried pipes is of great importance since it is fundamental for leakage detection, pipeline maintenance, and pipeline repair. The vibro-acoustic locating method, as one of the most effective detection technologies, has been studied by many researchers. However, previous studies have mainly focused on vibro-acoustic propagation in buried water pipes. Limited res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the feasibility of this method may be different for various in-pipe medium and pipe materials. Studies on the feasibility of the pipe excitation method in locating buried gas pipe has been conducted in [127]. The numerical results revealed that vibro-acoustic detection may not work well in gas pipe detection because of the weak coupling between gas and pipe wall, making the gas-dominated wave not radiate into the surrounding soil as effectively as the water-dominated wave.…”
Section: In Pipe Medium and Pipe Materialsmentioning
confidence: 99%
“…However, the feasibility of this method may be different for various in-pipe medium and pipe materials. Studies on the feasibility of the pipe excitation method in locating buried gas pipe has been conducted in [127]. The numerical results revealed that vibro-acoustic detection may not work well in gas pipe detection because of the weak coupling between gas and pipe wall, making the gas-dominated wave not radiate into the surrounding soil as effectively as the water-dominated wave.…”
Section: In Pipe Medium and Pipe Materialsmentioning
confidence: 99%
“…Depending on the difference in wave propagation velocity between the pipe and the underground, the pressure waves contribution is more or less attenuated but the shear waves contribution stays high. Moreover, we consider that the pipe is analogous to a cylindrically secondary source which radiates through the heterogeneous ambiant medium to receivers (geophones) [5,6]. To support this assumption, we can observe the experimental measurements presented below (Sect.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the surrounding medium effectively adds mass to the pipe wall, whereas the shear properties of the soil effectively add stiffness. The model described in [33] was further adapted by Liu et al [34] to investigate vibro-acoustic propagation in buried gas pipes. They proposed an effective radiation coefficient to measure the radiation of the gas-dominated and shelldominated waves.…”
Section: Introductionmentioning
confidence: 99%